Does tapentadol affect sex hormone concentrations differently from morphine and oxycodone? An initial assessment and possible implications for opioid-induced androgen deficiency - Eichenbaum, PhD, Gary; Göhler, MD, Karin; Etropolski, MD, Mila; Steigerwald, MD, PhD, Ilona; Pergolizzi, MD, Joseph; Kim, PhD, MA, Myoung; Vorsanger, PhD, MD, Gary (Journal of Opioid Management, 2015)
Objectives: Opioid-induced androgen deficiency (OPIAD) affects patients treated with opioid analgesics. The norepinephrine reuptake inhibitor (NRI) and μ-opioid receptor (MOR) agonist activities of tapentadol may result in tapentadol having less effect on serum androgen concentrations than analgesics acting through the MOR alone, such as morphine and oxycodone. The objectives of this publication are to 1) evaluate the effects of tapentadol (NUCYNTA and NUCYNTA extended release [ER]) on sex hormone concentrations in healthy male volunteers (vs placebo and morphine) and patients with osteoarthritis (vs placebo and oxycodone), and 2) present a mechanistic hypothesis explaining how the combined MOR agonist and NRI activities of tapentadol may result in less impact on androgen concentrations. Methods: Three clinical studies were conducted: study 1 (single-dose comparison study vs morphine in healthy volunteers), study 2 (single-dose-escalation study in healthy volunteers without an active comparator), and study 3 (multiple-dose study vs oxycodone in patients with osteoarthritis). Studies 1 and 2 were conducted at medical research centers in Germany and the United Kingdom; study 3 was conducted at primary and secondary care centers and medical research centers in the United States. All three studies were randomized, double blind, and placebo controlled. Concentrations of testosterone, luteinizing hormone (LH), and follicle-stimulating hormone (FSH; study 3 only) were evaluated at 6 and 24 hours postdose in studies 1 and 2, respectively, and at varying time points postdose in study 3. Results: In study 1, mean serum total testosterone concentrations in healthy male volunteers were similar at baseline for all treatment periods; 6 hours after dosing, mean concentrations were comparable between placebo (8.6 nmol/L) and tapentadol immediate release (IR; 43 mg, 8.8 nmol/L; 86 mg, 9.3 nmol/L), but were lower following administration of morphine IR 30 mg (5.4 nmol/L). In study 2, there were no or minimal changes in testosterone in the therapeutic dose range with tapentadol IR (75-100 mg), and there was a modest decrease that appeared to level off in the supratherapeutic range (125-175 mg); mean testosterone and LH concentrations with all doses remained within normal ranges (testosterone, 4.56-28.2 nmol/L; LH, 2.9-4.6 U/L). In study 3, the decrease in the mean [standard deviation] testosterone concentration from baseline to endpoint for male patients receiving tapentadol ER (100 mg, −1.9 [0.71] nmol/L; 200 mg, −2.1 [0.93] nmol/L) was numerically smaller compared to oxycodone CR (20 mg, −2.7 [0.93] nmol/L), but higher compared to placebo (−0.3 [1.62] nmol/L). Conclusions: These results suggest that tapentadol, which has combined MOR and NRI activities, may have a lower impact on sex hormone concentrations than pure opioid analgesics, such as morphine or oxycodone. The data and mechanistic rationale presented herein provide a justification for conducting additional hypothesis testing studies, and are not intended to be used as a basis for clinical decision making. Future studies may help elucidate whether the observed trends are clinically significant and would translate into a reduced incidence of OPIAD.